Memoirs of Vaidyas The Lives and Practices of Traditional Medical Doctors in Kerala, India V - T SUTOMU Y AMASHITA and P. R AM MANOHAR (eJournal of Indian Medicine, 2011)
This article presents an English translation of interview with a doctor of traditional Indian medicine (Āyurveda), Nī*** Nampūtiri (1945~2006) in Kerala, India. The interviewee’s specialized field is traditional psychiatry (bhūtavidyā) in Āyurveda. The contents of the interview are: 1. Background and History of the Family; 2. The Four limbs of Treatment and the Society; 3. Textual Tradition; 4. Diagnosis and Treatment of Mental Diseases; 5. ‘Wandering Lunatics’; 6. The body and the Mind; 7. Understanding of the Mind.